2017
DOI: 10.1021/acsphotonics.7b00768
|View full text |Cite
|
Sign up to set email alerts
|

Fully Suspended Reduced Graphene Oxide Photodetector with Annealing Temperature-Dependent Broad Spectral Binary Photoresponses

Abstract: A series of fully suspended reduced graphene oxide (RGO) photodetectors were fabricated based on free-standing thermally reduced graphene oxide (GO) thin films with various annealing temperatures (from 200 to 1000 °C). A new phenomenon was found that under ultraviolet (375 nm) to near-infrared (1064 nm) lasers irradiations, the photodetector consisting of fully suspended thermally reduced graphene oxide thin film and Au interdigital electrodes possess positive or zero or negative response depending on the anne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 39 publications
(71 reference statements)
3
27
0
Order By: Relevance
“…4e. R is almost invariable at~0.7 mA W −1 , which is numerically comparable to the response of samples obtained by other reduction methods (e.g., chemical and thermal) and much larger than that of typical photoreduced samples [31][32][33] . However, the photoresponse speed of our samples is relatively slow, as shown by the temporal measurement in Fig.…”
Section: On-chip Anisotropic Photoelectric Device Fabricationsupporting
confidence: 74%
See 2 more Smart Citations
“…4e. R is almost invariable at~0.7 mA W −1 , which is numerically comparable to the response of samples obtained by other reduction methods (e.g., chemical and thermal) and much larger than that of typical photoreduced samples [31][32][33] . However, the photoresponse speed of our samples is relatively slow, as shown by the temporal measurement in Fig.…”
Section: On-chip Anisotropic Photoelectric Device Fabricationsupporting
confidence: 74%
“…Our devices can realize stable photoresponsivity (R~0.7 mA W −1 ) even when exposed to light with low power (0.1 mW). This is numerically comparable to the response of samples obtained by other reduction methods (e.g., chemical and thermal) but is much larger than that of typical photoreduced samples [31][32][33] . In addition, the different reduction degrees of rGO along and vertical to the grating structures lead to its in-plane effective refractive indexes being different in the two directions, which in turn lays the foundation for the anisotropic response of rGO photodetectors 34 .…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Since pristine GO is a dielectric with low electronic conductivity and light absorption, it cannot be directly used for photo detection. Nevertheless, the reduction of GO is a more scalable and cost-effective approach for mass production of graphene-like materials as compared with the traditional mechanical and vacuum-based preparation methods, enabling many PDs based on rGO [171][172][173][174][175][176][177][178][179][180][181][182][183][184]. Moreover, rGO also has its own advantages such as high flexibility in engineering its material properties and great compatibility with a variety of substrates.…”
Section: Photodetectors (Pds)mentioning
confidence: 99%
“…18(e)), which allowed efficient transfer of photogenerated charge carriers and ultimately resulted in high photo responsivity (1520 mA/W) and fast response time (on the order of 10 -3 s). In 2017, Gan et al [183] demonstrated fully suspended rGO PDs with different annealing temperatures (Fig. 18(f)…”
Section: Photodetectors (Pds)mentioning
confidence: 99%